The Effect of Entrepreneurial Literacy and Self-Efficacy on Entrepreneurial Intention of Entrepreneurship Students at Univesitas Negeri Makassar - Fajriani Azis (Fakultas Ekonomi dan Bisnis Universitas Negeri Makassar, 2023)
This study aims for know influence literacy entrepreneurship and efficacy self in a manner partial and simultaneous to entrepreneurial intention of entrepreneurship student at Universitas Negeri Makassar. This study categorized as as study descriptive quantitative with population as many as 255 students. Determination sample use technique propionate stratified random sampling and obtained as many as 72 students. Obtained data through distribution questionnaire with likert scale. The analytical technique used is analysis statistics descriptive and analysis statistics inferential. The results showed that both partially and simultaneously, entrepreneurial literacy and self-efficacy have a positive and significant effect on entrepreneurial intention of entrepreneurship student at Universitas Negeri Makassar. The results of the study mean that the higher the entrepreneurial literacy and self-efficacy of students, both partially and simultaneously, it will increase the entrepreneurial intention of entrepreneurship student at Universitas Negeri Makassar.